Short communication: Molecular epidemiology of Streptococcus agalactiae differs between countries (2017)
ABSTRACT: Group B Streptococcus or Streptococcus agalactiae continue to be challenging for milk quality programs in countries with emerging dairy industries, such as Colombia, where high prevalence has been reported. Molecular typing of isolates is needed to understand the variability and epidemiology of this pathogen and to develop effective control and eradication programs. We characterized the molecular profile of Strep. agalactiae isolated from cows with subclinical mastitis in 21 Colombian dairy herds and measured diversity within and between herds using multilocus sequence typing. Isolates belonged to sequence type 248 [clonal complex (CC) 103; n = 30), ST1 (CC1; n = 6) or ST22 (CC22; n = 4)], whereas members of CC67/61, the dominant type in North America, were not detected. Presence of multiple clonally unrelated sequence type within a herd was common, which contrasts with the situation in European countries and suggests introduction from multiple sources. Our results demonstrate that conclusions from molecular epidemiological studies in 1 region cannot necessarily be extrapolated to other regions, and no single bovine-adapted CC of Strep. agalactiae exists in Colombia. Improvements in internal and external biosecurity will be needed to reduce Strep. agalactiae prevalence in Colombian dairy herds.